Growth of p-type GaAs∕AlGaAs(111) quantum well infrared photodetector using solid source molecular-beam epitaxy - Li, H. (2013)
A p-type GaAs/AlGaAs multi-quantum-well infrared photodetector(QWIP) was fabricated on a GaAs (111)A substrate by molecular-beam epitaxy using silicon as dopant. The same structure was also grown on a GaAs (100) wafer simultaneously to compare the material and structural properties. It was found that Si acts as a p-type dopant in the GaAs (111)A sample while it is -type in the GaAs (100) counterpart. The growth rate was found to be appreciably enhanced for GaAs (111)A compared with that of GaAs (100) orientation, while the Al composition in the barriers was found to be 20% smaller for a (111) orientation which results in a smaller barrier height. A peak responsivity of 1mA/W with a relatively wide wavelength response (∆ ? / ?p ~53%) was observed for the GaAs (111)A QWIP, mainly due to the location of the excited state far above the barrier. The photoresponse also showed a relatively strong normal incident absorption probably originating from the mixing of the conduction and valence Bloch states. The optimization of the quantum well parameters should further enhance the responsivity of this p-type QWIP with Si as dopant species.